The Impact of Censorship on the Soviet Canon of English Literature in Translation: A Case Study of Joseph Conrad - Valentinavičienė, Daina (Vertimo studijos, 2022)
The article gives an overview of translations of Joseph Conrad’s works into Lithuanian during the Soviet period (1940–1990), in an attempt to answer the question why some important titles belonging to the English Conradian canon had not been translated. Conrad’s Lithuanian translations are discussed in the broader context of translations into Russian in the former USSR, comparing to what extent the processes were similar and where they differed. On the basis of Soviet literary criticism, official publications in Russian and in Lithuanian, and paratexts in published translations, the article traces how the image of Conrad and his works was constructed for the Soviet readership. The article concludes that Conrad’s case was a form of less obvious (invisible) censorship when the writer is not banned, but through a careful selection of works for translation relegated to a narrow genre niche and ousted to the periphery of the Soviet canon of translated classical English literature. His socio-political novels (Secret Agent among them) were eliminated from translation into Lithuanian precisely because of their direct or indirect references either to Russia or to political themes. The comparison of Conrad’s bibliographies in translation reveals that Conrad’s presence in Lithuanian translations and literary research is markedly smaller than in Russian, which suggests that Conrad’s works were deemed more undesirable and access to them more restricted in one of the Western republics of the Soviet state than in its centre.
Keywords: Soviet English literature canon; Joseph Conrad; translations into Lithuanian; The Secret Agent; Soviet censorship and translation; invisible censorship